KEJAWEN SCIENCE IN JAVANESE MARRIAGE AND ITS IMPLICATIONS FOR HOUSEHOLD HARMONY HOUSEHOLD HARMONY - A, M. Luthfi; Asnawi, Habib Shulton; Ismail, Habib; Zuhdi, M Nurdin (SMART: Journal of Sharia, Traditon, and Modernity, 2022)
This article discusses the application of kejawen science in marriage. The purpose of writing this article is why some Javanese people still believe and practice kejawen science, especially in marriage, whether kejawen science has an impact on household harmony. Type of qualitative article, object of research in Kotabaru Village, Central Lampung, phenomenological study approach method, primary data sources are parents of married couples, religious leaders and community leaders. Data collection techniques through observation, interviews and documentation. The results showed that the Javanese community still believes and applies kejawen science in marriage. The reason is that it is believed that married couples have different wetons, have conflicting characters and traits, so the implication is that marriage is full of conflict and ends in divorce. Believing in Islamic divination is contradictory and forbidden for the reason of polytheism.Keywords: Kejawen Science, Marriage, Household Harmony.